Communication as fundamental to the Doctor-Patient relationship - Wilde-Menozzi, W. (Acta Biomedica Atenei Parmensis, 2008)
Communication among doctors when making diagnoses, when communicating information to the patient, and when evaluating a doctor’s own satisfactions and frustrations in terms of practicing medicine is shown to be crucial to any definition of good medicine. The wide range of literature in English on the topic of doctors and good communication suggests that a focus on its importance could be a tool for learning and a source for sensitizing Italian doctors to its crucial role in healing. Doctors need to be aware of their power when they deal with patients. How words are used can play a major role in how a patient faces a longterm disease. Communication is fundamental to good medicine; its rewards are immeasurable for both patient and physician.